2021
DOI: 10.1002/solr.202100837
|View full text |Cite
|
Sign up to set email alerts
|

Record 1.1 V Open‐Circuit Voltage for Cu2ZnGeS4‐Based Thin‐Film Solar Cells Using Atomic Layer Deposition Zn1‐xSnxOy Buffer Layers

Abstract: The Cu2ZnGe X Sn1‐X S4 (CZGTS) thin‐film solar cells have a limited open‐circuit voltage (V OC) due to bulk and interface recombination. Since the standard CdS buffer layer gives a significant cliff‐like conduction band offset to CZGTS, alternative buffer layers are needed to reduce the interface recombination. This work compares the performance of wide bandgap Cu2ZnGeS4 (CZGS) solar cells fabricated with nontoxic Zn x Sn1–x O y (ZTO) buffer layers grown by atomic layer deposition under different conditions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…All three groups reported the expected wider bandgap (1.8-2.2 eV) and evolution with regards to composition. [56][57][58] However, as compared to the studies about two-step-processed CZGSe discussed above, these investigations about CZGS showed more evidence of detrimental secondary phases, mainly ZnS, and an overall reduced grain size, potentially explained by the higher volatility of S making grain growth more challenging. Particular attention should be drawn to these aspects to reach a highquality CZGS material, e.g.…”
Section: Vacuum-based Depositionmentioning
confidence: 78%
See 1 more Smart Citation
“…All three groups reported the expected wider bandgap (1.8-2.2 eV) and evolution with regards to composition. [56][57][58] However, as compared to the studies about two-step-processed CZGSe discussed above, these investigations about CZGS showed more evidence of detrimental secondary phases, mainly ZnS, and an overall reduced grain size, potentially explained by the higher volatility of S making grain growth more challenging. Particular attention should be drawn to these aspects to reach a highquality CZGS material, e.g.…”
Section: Vacuum-based Depositionmentioning
confidence: 78%
“…57 CZGS thin films were also processed from sputtered CuS/Ge/ZnS precursors on glass/Mo/TiN and then sulfurized, which led to the formation of detrimental secondary phases, ZnS in particular, but also Ge- and Sn-related oxides. 58 These oxide phases were successfully etched by KCN surface treatment.…”
Section: Thin Filmsmentioning
confidence: 99%
“…In ref. 39, we showed that exchange of CdS with ZnSnO by atomic layer deposition gives increased V OC for CZGS devices, with voltages of up to 1.1 V. Since the band gap energy and position of the conduction band can be tuned for ZTO, optimisation of this buffer layer for alloyed CZGTS with band gap energy around 1.7 eV should be possible and is recommended for future work. This could also be combined with the use of Al 2 O 3 back contact passivation layers including NaF treatment as shown in this work to optimise the back contact.…”
Section: Discussion and Outlookmentioning
confidence: 92%
“…Introduction of adhesive TiN layers between Mo and CZGS improved adhesion, but only CZGS absorbers were fabricated, not alloyed CZGTS. 39 The conduction band alignment between CdS and CZTS is known to be non-ideal (negative), and to be even worse with Ge-alloying since most of the band gap increase with Ge-alloying is in the conduction band. In ref.…”
Section: Resultsmentioning
confidence: 99%
“…Quaternary copper-bearing sulfides and selenides of Cu 2 B II D IV X 4 type (B II represents zinc, cadmium, and mercury; D IV is silicon, germanium, or tin; while X stands for sulfur and selenium) attract enormous attention during the recent two decades from engineering and scientific outlooks because they feature numerous prospective practical applications. Many sulfides and selenides of Cu 2 B II D IV X 4 type demonstrate p-conductivity with band gap values being in the energy range of 1.0–1.56 eV, significant absorption coefficient values exceeding 10 4 cm –1 , rather big conversion power, etc. The above physicochemical properties make the Cu 2 B II D IV X 4 -type chalcogenides, in many cases, germanium-containing sulfides and selenides, very attractive compounds for practical use as effective absorbers for new-generation photovoltaic thin-film solar cell technologies, prospective thermoelectric materials, photocatalysts of conversion reactions, and semiconductors with promising electrical transport properties. , Many Cu 2 B II D IV X 4 -type compounds crystallize in noncentrosymmetric structures; therefore, they attract attention as efficient nonlinear optical semiconductors . The important advantage of Cu 2 B II D IV X 4 -type chalcogenides is that a number of their physical and chemical properties, in particular, photovoltaic, transport, and thermoelectric behaviors, can be efficiently tuned to gain wishful technological magnitudes through doping them with other atoms, , synthesis of solid solutions, formation of peculiar point vacancies and intrinsic defects, , changing the dimensions of the crystals to nanosize values by formation of nanocrystals with controlled compositions, , nanowire arrays, , and nanorods .…”
Section: Introductionmentioning
confidence: 99%